CAPITAL STRUCTURE AND ITS IMPACT ON PROFITABILITY: A STUDY OF LISTED MANUFACTURING COMPANIES IN SRI LANKA - Brabete, B.; Nimalathasan, B. (My University, 2010)
Capital structure is one of the most complex areas of financial decision making due to its interrelationship with other financial decisions variables. Capital structure is the composition of debt and equity capital that comprise a firm’s financing its assets and can be rewritten as the sum of net worth plus preferred stock plus long-term debts. In this study an attempt has been made to analyze the capital structure and its impact on profit earning capacity during 2003 to 2007 (05 years) financial year of listed manufacturing companies in Sri Lanka. The results shows that debt to equity ratio (D/E) ratio is positively and strongly associated to all profitability ratios [gross profit ratio (GPR); operating profit ratio(OPR); and net profit ratio(NPR)] except return on capital employed (ROCE) and return on investment (ROI). Debt to assets (D/A) ratio is positively and strongly associated to OPR, NPR and ROCE. Similarly capital gearing (CG) ratio is also positively correlated to GPR and NPR. Further, interest coverage (IC) ratio is significantly correlates to ROCE and NPR. Further capital structure has a great impact on all profitability ratios except ROCE and ROI. The outcomes of the study may guide entrepreneurs, loan- creditors and policy planners to formulate better policy decisions in respect of the mix of debt and equity capital and to exercise control over capital structure planning and thereby to control and reduce bankruptcy costs.